PENGARUH LOGISTIK DAN KEAMANAN DATA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SAMSUNG PADA E-COMMERCE TOKOPEDIA DALAM SITUASI COVID-19 - M. Ikbal Setiawan, Ikbal (2022)
his research is a quantitative study carried out with the aim of knowing and proving the effect of logistics and security data on purchasing decisions for Samsung smartphone products on Tokopedia e-commerce in the Covid-19 situation involving 100 respondents. The sampling technique used is Non-Probability Sampling. Assistance application when the data uses smartPLS 3.0 by performing the t-test and R-test. The logistic variable is shown by the original results until Logistics gets a value of 0.363. From the statistical test t shows the results tcount 3,423 > t table 1,98472, then logistics has an influence on purchasing decisions. This is in line with the significance value through P Values of 0.001 < 0.05, which means that the logistics variable has a positive and significant effect on the purchasing decision variable, or in other words H1 is acceptable. From the test results on the data security variable on purchasing decisions also has a positive influence. This is indicated by the results of the original sample on data security obtaining 0.583. From the results of the statistical test data processing t shows the results tcount 5,613> t table 1,98472, it can be said that data security has an influence on purchasing decisions. This is in line with the significance value through P Values of 0.000 <0.05, which means that the data security variable has a positive and significant effect on the purchasing decision variable, or in other words H2 is acceptable